DEVELOPMENT OF THE ENTERPRISE MANAGEMENT SYSTEM THROUGH THE IMPLEMENTATION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS - Nataliia Svichkar; Hanna Kusnetsova; Kostiantyn Zhyzhko (Economics & Education, 2023)
Explain the concept of consolidated financial statements, parent company, subsidiary company according to international and national standards. To study the composition of consolidated reports, the consolidation process, the principles of consolidation. Study the types of controlled entities, taking into account the proportion of voting rights held by the investor and the standards that govern them. Define the concept of control according to international standards and identify the factors that influence the determination of whether the investor controls the investee. The purpose of the paper is to develop methodological and practical recommendations for preparing group management reporting in accordance with international standards. Consolidated reporting should be prepared to identify the results of the analysis of the state and activities of the holding, there is a need to transform consolidated reporting in accordance with IFRS for entering the international market and attracting foreign investment. Methodology. The research is based on the application of general scientific techniques and methods. The methods of detailing, analysis and synthesis, deductive and inductive approach have been used to clarify the concept of "IFRS". The methods of selective observation and historical argumentation of the researched problems are applied – to generalise the unsolved problems of IFRS. Results. Consolidated financial statements undoubtedly contain important information for making financial and management decisions. Intra-group transactions can give an unrealistic picture of the activities of a group of companies, their sales, calculations, stocks and financial results; therefore, consolidated reporting gives a more objective picture of the operations and financial status of a single economic unit and does not replace the individual financial reports of group companies, since transactions between group members are not taken into account during consolidation. Practical implications. The concepts of consolidated financial statements, parent company, subsidiary company according to international and national standards are revealed. The composition of the forms of consolidated reporting, the consolidation procedure, the principles of consolidation are considered. The types of controlled entities, taking into account the investor's share of voting rights, and the standards governing them are presented. The concept of control in accordance with international standards is defined and the factors influencing the determination of whether the investor controls the investee are presented. Value/originality. Methodological and practical recommendations have been developed for the preparation of group management reporting in accordance with international standards.